Hero - Lupica, Mike (New York Philomel Books, 2010)
Fourteen-year-old Zach learns he has the same special abilities as his father, who was the President's globe-trotting troubleshooter until "the Bads" killed him, and now Zach must decide whether to use his powers in the same way at the risk of his own life.
Keywords: Heroes and heroines -- Fiction; Father-son relationship -- Fiction; Politics -- Fiction; Death -- Fiction; Family life -- Fiction -- New York (N.Y.); New York (N.Y.) -- Fiction